Effectiveness of Long Bean Plant Pest Control by Utilizing Cyanic Acid Content from Various Parts of Rubber Cassava Plants (Manihot Glaziovii) - Siti Mardhika Sari; Endang Suprapti; Tyas SKD; Achmad Fatchul Aziez; Nonik Fitri Cahyani (Journal of Biodiversity and Biotechnology, 2024)
Pest attacks are one of the main obstacles in the cultivation of long beans (Vigna unguiculata ssp. sesquipedalis) in Indonesia. This study aims to evaluate the effectiveness of cyanide acid content from various parts of the rubber cassava plant (Manihot glaziovii) in controlling Aphis craccivora pests and its impact on the growth and yield of long beans. The study was conducted in Sragen and the Laboratory of the Faculty of Agriculture, Tunas Pembangunan University, Surakarta during September–December 2024 with a completely randomized block design (RAKL) with two factors, namely plant parts (leaves, tuber skin, and tubers) and extract doses (0, 10, 20, and 30 ml/plant). The results showed that tuber skin fermentation (B2) was the most effective in reducing the percentage of pest attacks (30.80%) and attack intensity (40.44%). The treatment dose of 30 ml/plant (K4) gave the best results in suppressing pest attacks and increasing growth and yield parameters, such as plant length (141.64 cm), fresh stalk weight (1905.77 g), and fruit weight (497.22 g). The bioactive content in cassava tuber skin has the potential as a pest control agent as well as a plant growth stimulant. This study supports the use of environmentally friendly and sustainable local biopesticides to increase the productivity of long beans.